2022
DOI: 10.3390/v14091930
|View full text |Cite
|
Sign up to set email alerts
|

Selective Electrochemical Detection of SARS-CoV-2 Using Deep Learning

Abstract: COVID-19 has been in the headlines for the past two years. Diagnosing this infection with minimal false rates is still an issue even with the advent of multiple rapid antigen tests. Enormous data are being collected every day that could provide insight into reducing the false diagnosis. Machine learning (ML) and deep learning (DL) could be the way forward to process these data and reduce the false diagnosis rates. In this study, ML and DL approaches have been applied to the data set collected using an ultra-fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“… The proposed model showed the need for an improved model which may state-of-the-art methods for pandemic detection and prediction. However, the outcome shows the need for further investigation [ 41 ] The dataset was gathered with the help of an incredibly quick COVID-19 diagnostic sensor, and DL methods have been used. Covid-19 dataset CNN NA The findings suggest that SARS-CoV-2 samples may be correctly identified by the CNN algorithm with a 96.15% sensitivity 98.17% specificity and 97.20% accuracy respectively By combining this DL-based model with the already-existing UFC-19, SARS-CoV-2 presence could be better detected.…”
Section: Results and Analysismentioning
confidence: 99%
See 1 more Smart Citation
“… The proposed model showed the need for an improved model which may state-of-the-art methods for pandemic detection and prediction. However, the outcome shows the need for further investigation [ 41 ] The dataset was gathered with the help of an incredibly quick COVID-19 diagnostic sensor, and DL methods have been used. Covid-19 dataset CNN NA The findings suggest that SARS-CoV-2 samples may be correctly identified by the CNN algorithm with a 96.15% sensitivity 98.17% specificity and 97.20% accuracy respectively By combining this DL-based model with the already-existing UFC-19, SARS-CoV-2 presence could be better detected.…”
Section: Results and Analysismentioning
confidence: 99%
“…The global economy has collapsed due to the coronavirus (COVID-19) pandemic [ 1 , 22 , 41 ]. New strain variants, a lack of social self-control, and optional vaccination all increase the likelihood that COVID-19 will persist and behave like a seasonal sickness.…”
Section: Introductionmentioning
confidence: 99%
“…This strategy has the potential to completely transform the field of biosensing and showed considerable promise in terms of enhancing the precision and dependability of biosensors, notably in the context of non-invasive SARS-CoV-2 testing. Specific examples will be given in Section 4 of using supervised algorithms such as SVMs to improve SARS-CoV-2 biosensors by recognizing specific patterns in a dataset and assigning the data to the correct class [ 37 , 38 ].…”
Section: Machine Learning-enhanced Biosensors For Non-invasive Samplingmentioning
confidence: 99%
“…The highest achieved accuracy was 97.2%, which outperformed the DTC algorithm. They suggested that combining this CNN model with UFC-19 could enable selective identification of SARS-CoV-2 presence within two minutes [ 38 ].…”
Section: Applications Of Machine Learning-enhanced Biosensors For Sar...mentioning
confidence: 99%